Ungedruckte Briefe (1618, 1653-1661) des jungen Heidelberger Hofsekretärs bzw. des alten pfälzischen Dichters und zweibrückischen Hofrats und Präfekten Balthasar Venator (1594-1664) = Unprinted letters (1618, 1653-1661) from the young court secretary in Heidelberg, i.e. the old Palatinate poet, Zweibrücken-based court counsellor and prefect Balthasar Venator (1594-1664) - Kühlmann, Wilhelm (Daphnis, 2022)
Abstract The letters edited here do complete the Gesamtausgabe (Heidelberg 2001) of Balthasar Venator’s works and letters. The author was a friend of Martin Opitz, scholar, poet, biographer, satirist and high ranking court counsellor and prefect of Meisenheim in Pfalz-Zweibrücken. The first three letters to the Heidelberg Professor Janus Gruter (written around 1618) are edited, translated and commented. In addition, this edition presents letters from Venators late period to the friend and pastor Johann Adam Michaelis (written 1653-1661). The early letters shed a light on the scholarly atmosphere before the big war, the later ones illustrate familiar and local events, they also show Venator as writer of the Dukes diplomatic correspondence and as translator. Thus, mentalities within the administrative elite of the princely state are being documented. Venators report of - sometimes comical - court cases show the genuine calvinistic cooperation of secular law and clerical Sittenzucht.
Gesehen am 02.01.2023
Keywords: Venator, Balthasar -- 1594-1664; Brief; Gruterus, Janus; Venator, Balthasar